2019
DOI: 10.1002/ajmg.a.61439
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study of physical activity and quality of life in adolescents with Turner syndrome

Abstract: Women with Turner syndrome (TS) have a high morbidity from both medical and psychological conditions with a negative impact on quality of life (QoL). Physical activity is a modifiable behavior shown to reduce risk for these chronic medical and mental health conditions and enhance QoL in other populations. Limited research suggests that adolescents and women with TS are less likely to engage in or enjoy physical activity than peers. This mixed methods study aimed to document physical activity levels in a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…While women with TS were as active as women from the SHS, both groups adhered poorly to recommendations for the healthy adult population for Switzerland, 13 from the CDC 14 and the WHO 15 . Our results are similar to those from a study of the University of Colorado, USA, where only 19% of girls with TS adhered to the recommendations of 1 h per day of moderate‐to‐vigorous physical activity 10 . A study from Poland found that girls with TS aged 10–18 years had a lower performance in fitness tests than healthy controls 16 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…While women with TS were as active as women from the SHS, both groups adhered poorly to recommendations for the healthy adult population for Switzerland, 13 from the CDC 14 and the WHO 15 . Our results are similar to those from a study of the University of Colorado, USA, where only 19% of girls with TS adhered to the recommendations of 1 h per day of moderate‐to‐vigorous physical activity 10 . A study from Poland found that girls with TS aged 10–18 years had a lower performance in fitness tests than healthy controls 16 .…”
Section: Discussionsupporting
confidence: 88%
“…15 Our results are similar to those from a study of the University of Colorado, USA, where only 19% of girls with TS adhered to the recommendations of 1 h per day of moderate-tovigorous physical activity. 10 A study from Poland found that girls with TS aged 10-18 years had a lower performance in fitness tests than healthy controls. 16 Women with TS are often smaller, heavier and have delayed puberty compared with their peers and have to cope with medical and psychosocial difficulties, which might Persons with chronic morbidities such as cardiovascular disease are at risk of being physically inactive, which leads to a cycle of deconditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These PROMIS® global health measures have been validated in the general population (Forrest et al, 2014(Forrest et al, , 2016. PROMIS® measures have been used in arthrogryposis, Turner syndrome and neurologic conditions including epilepsy and Parkinson's disease (Shulman et al, 2019;Thompson et al, 2020;Wall et al, 2020).…”
Section: Instrumentsmentioning
confidence: 99%
“…A US study by Thompson et al found that only four of 21 girls aged 12-21 years met the target of one hour per day. 8 Milde and colleagues from Poland compared 184 girls with Turner syndrome aged 10-18 years with 280 controls and found that while the patient group performed better at some tasks, differences in body habitus rendered other motor tasks more difficult. 9 Clearly, much work is needed in helping define activity guidelines which are appropriate for young people with Turner syndrome and which can be usefully documented annually in the manner that we are suggesting for adult patients.…”
mentioning
confidence: 99%